2019
DOI: 10.1038/s41467-019-12658-9
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness-specific dynamic interactions of brain integration and functional diversity

Abstract: Prominent theories of consciousness emphasise different aspects of neurobiology, such as the integration and diversity of information processing within the brain. Here, we combine graph theory and dynamic functional connectivity to compare resting-state functional MRI data from awake volunteers, propofol-anaesthetised volunteers, and patients with disorders of consciousness, in order to identify consciousness-specific patterns of brain function. We demonstrate that cortical networks are especially affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
388
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 208 publications
(431 citation statements)
references
References 70 publications
(130 reference statements)
35
388
8
Order By: Relevance
“…Our findings suggest that regions of the default mode and executive control (sub)networks may be able to support human higher cognition precisely thanks to their extensive involvement with synergistic processing. Intriguingly, the high-synergy DMN is involved in self-related cognitive processes 26,27 , and it is also especially disrupted by loss of consciousness, whether caused by anaesthesia or severe brain injury 28 . Indeed, the global workspace theory of consciousness posits that integration of information within a global workspace is necessary for consciousness 29 -and a formal link has also been established between synergy and the measure of consciousness known as integrated information 3,30 .…”
Section: Neurobiological Origins Of Synergy In the Human Brainmentioning
confidence: 99%
“…Our findings suggest that regions of the default mode and executive control (sub)networks may be able to support human higher cognition precisely thanks to their extensive involvement with synergistic processing. Intriguingly, the high-synergy DMN is involved in self-related cognitive processes 26,27 , and it is also especially disrupted by loss of consciousness, whether caused by anaesthesia or severe brain injury 28 . Indeed, the global workspace theory of consciousness posits that integration of information within a global workspace is necessary for consciousness 29 -and a formal link has also been established between synergy and the measure of consciousness known as integrated information 3,30 .…”
Section: Neurobiological Origins Of Synergy In the Human Brainmentioning
confidence: 99%
“…Relating subjective mental states to the underlying brain states remains a key challenge for contemporary neuroscience 1 . Despite recent advances, what remains elusive is a principled account of how the spatio-temporal brain dynamics that support consciousness [1][2][3][4][5][6][7] , arise from the interplay of cortical dynamics across the brain's anatomical connections 8 .…”
Section: Main Textmentioning
confidence: 99%
“…Therefore, computational and theoretical reasons converge to predict that propofol should induce connectome harmonic alterations that are the opposite of what is observed with psychedelics. To further establish whether the connectome harmonic signature of anaesthesia is representative of other ways of losing consciousness, we also considered a cohort of N=22 patients diagnosed with chronic disorders of consciousness arising from severe brain injury 3 . We investigated whether CHD could detect consciousness in a subset of patients who had previously exhibited evidence of covert consciousness by performing mental imagery tasks in the scanner 25,26 (in terms of specific brain regions activating when patients were asked to imagine playing tennis or navigating around their house) (fMRI+; N=8), compared with patients who had provided no such evidence (fMRI-; N=14).…”
Section: Connectome Harmonic Signatures Of Consciousnessmentioning
confidence: 99%
“…In addition to the altered static functional connectivity within and between the RSNs, recent studies of anesthetic-induced sedation or unconsciousness have focused on functional brain dynamics and connectivity patterns [ 92 95 ]. One recent study combined graph theory and dynamic functional connectivity to compare resting-state functional MRI data from propofol-anesthetised volunteers and patients with disorders of consciousness, in order to identify consciousness-specific patterns of brain function [ 94 ]. The authors demonstrated that loss of consciousness (whether due to propofol anesthesia or traumatic brain injury) is accompanied by reduced functional diversity and integrative capacity in the posterior regions of the brain’ s DMN, especially during temporal states of high integration [ 94 ].…”
Section: Functional Connectivity During Midazolam-induced Sedationmentioning
confidence: 99%